Crystallization behavior and isothermal crystallization kinetics of PLLA blended with ionic liquid, 1‐butyl‐3‐methylimidazolium dibutylphosphate. Issue 3 (20th August 2014) - Wei, Taiyan; Pang, Sujuan; Xu, Nai; Pan, Lisha; Zhang, Zhengqing; Xu, Ruizhang; Ma, Nansong; Lin, Qiang
ABSTRACT The crystallization behavior and isothermal crystallization kinetics of neat poly(l‐lactic acid) (PLLA) and PLLA blended with ionic liquid (IL), 1‐butyl‐3‐methylimidazolium dibutylphosphate, were researched by differential scanning calorimetry (DSC), polarizing optical microscopy (POM), and wide angle X‐ray diffraction (WXRD). Similar to the non‐isothermal crystallization behavior of neat PLLA, when PLLA melt was cooled from 200 to 20°C at a cooling rate of 10°C min−1, no crystallization peak was detected yet with the incorporation of IL. However, the glass transition temperature and cold crystallization temperature of PLLA gradually decreased with the increase of IL content. It can be attributed to the significant plasticizing effect of IL, which improved the chain mobility and cold crystallization ability of PLLA. Isothermal crystallization kinetics was also analyzed by DSC and described by Avrami equation. For neat PLLA and IL/PLLA blends, the Avrami exponent n was almost in the range of 2.5–3.0. It is found that t1/2 reduced largely, and the crystallization rate constant k increased exponentially with the incorporation of IL. These results show that the IL could accelerate the overall crystallization rate of PLLA due to its plasticizing effect. In addition, the dependences of crystallization rate on crystallization temperature and IL content were discussed in detail according to the results obtained by DSC and POM measurements. It was verified by WXRD that the addition of IL could not change the crystal structure of PLLA matrix. All samples isothermally crystallized at 100°C formed the α‐form crystal. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41308.